Adults with intellectual disabilities and challenging behaviour: the costs and outcomes of in‐ and out‐of‐area placements. (4th April 2012) - Perry, J.; Allen, D. G.; Pimm, C.; Meek, A.; Lowe, K.; Groves, S.; Cohen, D.; Felce, D.
Abstract Background People with severe challenging behaviour are vulnerable to exclusion from local services and removal to out‐of‐area placements if locally available supported accommodation is insufficient to meet their needs. There are concerns about the high costs and potentially poorer outcomes of out‐of‐area placements but relatively little is known about how costs and outcomes compare with provision for a similar population placed locally. Methods Costs, quality of care and a wide range of quality of life outcomes for 38 people with intellectual disabilities and challenging behaviour living in‐area and 38 similar people living out‐of‐area were compared. The two groups were matched as far as possible on risk factors for out‐of‐area placement. The out‐of‐area group represented two‐thirds of the total number of people who originated from the territory served by the largest specialist health service in Wales and were placed in residential settings at least 10 miles beyond its boundaries. Results There was a mixed pattern of quality of care and quality of outcome advantages between the two types of setting, although in‐area placements had a greater number of advantages than out‐of‐area placements. Unexpectedly, out‐of‐area placements had lower total costs, accommodation costs and daytime activity costs. Conclusions No overall conclusion could be reached about cost‐effectiveness. A number of potential reasons for the differences in cost were identified. Although additional resources may be needed to provide in‐area services for those currently placed out‐of‐area, government policy to provide comprehensively for those who want to live locally, irrespective of their needs, appears to be attainable.